TRLS-03. PHASE II TRIAL OF GDC-0084 IN COMBINATION WITH TRASTUZUMAB FOR PATIENTS WITH HER2-POSITIVE BREAST CANCER BRAIN METASTASES (BCBM). (12th August 2019) - Leone, Jose Pablo; Trippa, Lorenzo; Milisits, Lindsey; Andrews, Chelsea; Ligibel, Jennifer; Parsons, Heather; Bi, Wenya; Zhao, Jean; Winer, Eric; Lin, Nancy
Abstract: BACKGROUND: The PI3K/Akt/mTOR is an important pathway in BCBM. Mutations in PIK3CA or PTEN loss are associated with trastuzumab resistance. Inhibition of PI3K and mTOR led to durable responses in 3 of 5 patient-derived xenografts (PDX) models of BCBM. GDC-0084 is a potent, brain-penetrant inhibitor of class I PI3K and mTOR. METHODS: This is a single-center, phase II study to evaluate the efficacy of the combination of GDC-0084 with trastuzumab for the treatment of central nervous system (CNS) metastases in patients with HER2-positive breast cancer. Patients will receive GDC-0084 (45 mg daily) and trastuzumab (8 mg/kg loading dose, then 6 mg/kg every 3 weeks). Two cohorts will be enrolled: Cohort A: a single-arm, two-stage, phase II cohort; and Cohort B: a pre-surgical window cohort. Inclusion criteria include unequivocal evidence of new and/or progressive HER2-positive CNS metastases, at least one measurable (≥10 mm) CNS metastasis (Cohort A), clinical indication for CNS metastasis resection (Cohort B). Primary endpoint for Cohort A is objective response rate (ORR) in the CNS per Response Assessment in Neuro-Oncology Brain Metastases (RANO-BM) criteria. For Cohort B, the primary endpoint is the correlation between p4EBP1 levels in the resected CNS tumor tissue from patients and intracranial response to GDC-0084/trastuzumab in the PDX model generated from the same patient. Secondary endpoints include overall survival, safety and patient-reported outcomes. Mandatory blood and cerebrospinal fluid with optional tumor biopsy will be collected at baseline, on-treatment and at progression. In Cohort A, we will enroll 37 patients in a Simon two-stage design. If ≥4 responses are seen, the regimen will be considered successful. This design has 90% power with alpha < 10%. Cohort B will enroll 10 patients. The trial opened in February, 2019. NCT03765983.